LIVELIHOOD STRATEGY OF FORMER FEMALE MIGRANT WORKERS - Yustinus Wahyudi; Natalia Puji Rahayu; Gatot Sasongko (Universitas Tidar, 2021)
The life of female former migrant workers after working abroad is an interesting phenomenon to study. The contradiction in the conditions of life when working as a TKI and after working demands a strategy to maintain its survival. The purpose of this study is to analyze the survival strategies of women migrant workers after not working abroad. This type of research is a qualitative descriptive study and was conducted in Sarimulyo Village, Kebonagung District, Demak Regency. The type of data used is primary data. The technique of collecting data by interviewing direct sources. The research findings show that women former migrant workers use the livelihood strategy, namely human capital by relying on foreign language skills to teach lessons and courses as well as baking skills. Natural capital by managing rice fields and gardens. Social capital by borrowing from relatives and cooperatives. Financial capital using savings. Physical capital is by utilizing the paddy slip tool left by our parents and cake-making equipment to make pastries.